The odds of psychiatric hospitalization and sociodemographic characteristics of people with depression - Leonardo Naves dos Reis; Bruna Paiva do Carmo Mercedes; Adriana Inocenti Miasso; Edilaine Cristina da Silva Gherardi-Donato (Universidade Federal de Goias, 2013)
The objective was to verify the association between the need for psychiatric hospitalization and sociodemographic characteristics of mental health outpatients with depression. Descriptive statistics was performed. The patients' profiles were compared to the general health service clientele. Multiple logistics regression analysis was used to test the need for hospitalization considering independent variables (gender, ager and diagnosis). Regarding patients with depression, 82% were women, 74% had a low educational level, and 78% were 40 to 69 years old. An association was observed between the dependent variable and age (p=0.003) and depression (p=0.007); no association was observed for gender. These results contribute with the health team's search for intervention strategies aimed at the specific needs of this clientele and in guiding studies that elucidate the biopsychosocial aspects related to the profile of the most susceptible clientele, thus characterized as a first step to building the knowledge to rethinking mental health practices. Descriptors: Depression; Epidemiology; Mental Health; Psychiatric Nursing.